Leadership within the Muslim community in Britain: The role of followers in meeting needs and expectations - Naeem, Aamer (2007)
This research, conducted by means of qualitative surveys, looks at leadership within the Muslim community in Britain from the perspective of the followers and their role in the leadership process. Needs and expectations of Muslim followers and the extent to which these are being met are analysed and recommendations made.